Peran Voluntary Sector Pada Kegiatan Filantropi Pancasila Dalam Mengembangkan Kompetensi Kewarganegaraan Komunitas Kelas Negarawan Muda - Fitriasari, Susan; Kurniati, Pat; Sapriya; Darmawan, Cecep (Jurnal Civic Hukum, 2024)
Strengthening Pancasila philanthropy through the voluntary sector to develop civic competence is carried out on the basis of how existing Pancasila education learning is not only textual learning but must be contextual and become meaningful learning. The role of the younger generation in philanthropic activities is needed, where their involvement can change the gap that occurs in society. The presence of a volunteer Turun Tangan Community has practiced social philanthropy by conducting an educational movement called Kelas Negarawan Muda (KNM) as an effort to develop its Civic Competence, but the educational movement or activity needs to be adjusted to the values of Pancasila. The method used in this study is a qualitative descriptive method in exploring and describing how to strengthen Pancasila philanthropy through the voluntary sector to develop civic competence. Strengthening Pancasila philanthropy in the era of globalization can have a positive impact on the voluntary sector in developing its citizenship competence, as done through a project called Kelas Negarawan Muda (KNM).